2010
DOI: 10.5539/ijbm.v5n3p185
|View full text |Cite
|
Sign up to set email alerts
|

Leadership spirituality in Banking Professionals and its impact on Organizational Commitment

Abstract: Spirituality has been found as the key indicator in enhancing and increasing multiple levels of organizational success and accomplishment. The present study explores the relationship between the spirituality and Job satisfaction of 121 branch managers, area managers and regional managers of various private and public sector banks of Pakistan. For the purpose of study an independent spirituality assessment scale (iSAS) developed by Rojas (2002) was used. Spirituality is found quite significant in predicting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 21 publications
2
4
0
1
Order By: Relevance
“…For example, Rego and Pina e Cunha (2008) investigated the effects of workplace spirituality on organizational commitment and similar to our results they found that spiritual leadership is more effective on affective commitment rather than continuance commitment. Similarly, Usman and Danish (2010) examined leadership spirituality in banking sector, in parallel with our results in their study spiritual leadership has found to be very important in explaining the affective commitment of individuals. And Kazemipour, Amin and Pourseidi (2012) also investigated effects of spiritual leadership and they showed that workplace spirituality is effective on affective commitments of nurses.…”
Section: Discussionsupporting
confidence: 71%
“…For example, Rego and Pina e Cunha (2008) investigated the effects of workplace spirituality on organizational commitment and similar to our results they found that spiritual leadership is more effective on affective commitment rather than continuance commitment. Similarly, Usman and Danish (2010) examined leadership spirituality in banking sector, in parallel with our results in their study spiritual leadership has found to be very important in explaining the affective commitment of individuals. And Kazemipour, Amin and Pourseidi (2012) also investigated effects of spiritual leadership and they showed that workplace spirituality is effective on affective commitments of nurses.…”
Section: Discussionsupporting
confidence: 71%
“…This means that by applying a good spiritual leadership to affect the increased organizational commitment Private lecturer at the University of Islam in the city of Medan. The results are consistent with the results of research conducted by (Scott and Tweed, 2016), (Udin, Handayani and Bakhri, 2017), (Usman and Danish, 2010) and (Arshad and Abbasi, 2014), (Azlimin and Hakim, 2015) concluded that spiritual leadership influence on organizational commitment.…”
Section: Influence Of Spiritual Leadership On Organizational Commitmentsupporting
confidence: 91%
“…That is why spiritual transformation is vital, not only because of its collaboration to employees' personal growth, but also because of its ability to build a psychological contract between employer and employee by which the employee feels valued, either on or off his job (Dniel and Jardon, 2015; Ahiauzu and Asawo, 2012). Usman and Danish (2010) indicate that empowering the philosophy of spirituality, which counts on disseminating the universal values of ethics, norms, rules and guidance, in workplace aligns employees with their organizations for achieving success.…”
Section: Spirituality and Workplace Spiritualitymentioning
confidence: 99%
“…Over the last decade, workplace spirituality has gained a currency in both academia and work arenas. This intangible asset has a considerable effect on the long term survival and maintenance of any organization (Usman and Danish, 2010). According to Altaf and Awan (2011) tough competition which takes place in our current global and local markets has fostered companies to set very high targets for their employees.…”
Section: Introductionmentioning
confidence: 99%